2020
DOI: 10.1002/cphc.202000759
|View full text |Cite
|
Sign up to set email alerts
|

Configuration Flipping in Distal Pocket of Multidrug Transporter MexB Impacts the Efflux Inhibitory Mechanism

Abstract: MexAB-OprM efflux pumps, found in Pseudomonas aeruginosa, play a major role in drug resistance by extruding out drugs and antibiotic molecules from cells. Inhibitors are used to cease the potency of the efflux pumps. In this study, in-silico models are used to investigate the nature of the binding pocket of the MexAB-OprM efflux pump. First, we have performed classical molecular dynamics (MD) simulations to shed light on different aspects of protein-inhibitor interaction in the binding pocket of the pump. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Careful analyses of rmsd data of the porter domain consisting of PN1, PN2, PC1, and PC2 subdomains over the last 100 ns trajectory showed almost similar trends of average positional fluctuations. Also, the rmsd values were almost constant over time and within the accepted range of deviation , from the native protein structure (Supporting Information, Figure S7). Furthermore, the average rmsd values of the PN2 and PC1 subdomains were calculated for each ligand-bound AcrB and MexB system to gain insights about the structural changes of the DBP region.…”
Section: Resultsmentioning
confidence: 63%
“…Careful analyses of rmsd data of the porter domain consisting of PN1, PN2, PC1, and PC2 subdomains over the last 100 ns trajectory showed almost similar trends of average positional fluctuations. Also, the rmsd values were almost constant over time and within the accepted range of deviation , from the native protein structure (Supporting Information, Figure S7). Furthermore, the average rmsd values of the PN2 and PC1 subdomains were calculated for each ligand-bound AcrB and MexB system to gain insights about the structural changes of the DBP region.…”
Section: Resultsmentioning
confidence: 63%
“…Furthermore, we have observed that two channels among all, namely CH2 and CH5, are endowed with MFS in all the transporters (the latter mostly in MexY), suggesting their possible involvement in the early recognition of several small organic probes (and thus substrates, such as antibiotics, functionalized with these chemical groups). This is relevant also from a pharmaceutical perspective, as it points to the possibility of targeting these sites in drug design efforts (Collu et al, 2012;Kumar Roy and Patra, 2020)-for instance to inhibit the translocation of substrates from the periplasm to the AP L and DP T binding pockets-and protein engineering (Mao et al, 2002;Middlemiss and Poole, 2004;Krishnamoorthy et al, 2008;Ohene-Agyei et al, 2012;Wang et al, 2015;Kumar Roy and Patra, 2020;Marshall and Bavro, 2020;Zwama and Nishino, 2021;Cacciotto et al, 2022).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Binding free energies (Δ G bind ) of protein–ligand complexes were calculated by using molecular mechanics–generalized Born surface area (MM-GBSA) implicit solvent models. MM-GBSA is a more widely used method to date for calculation of the binding free energies among biomolecular complexes . The general MM-GBSA is used to determine significant conformational fluctuations and the entropic contribution to the binding energy.…”
Section: Methodsmentioning
confidence: 99%
“…MM-GBSA is a more widely used method to date for calculation of the binding free energies among biomolecular complexes. 70 The general MM-GBSA is used to determine significant conformational fluctuations and the entropic contribution to the binding energy. The binding free energy was calculated based on the following equations…”
Section: Trajectory Analysismentioning
confidence: 99%